Penerapan Bimbingan Kelompok dengan Teknik Permainan Untuk Menurunkan Tingkat Kecanduan Media Sosial - Nabilla Ashari Sulistyo; Rosa Imani Khan; Devi Asmindra Milasanty (CV. ITTC INDONESIA, 2025)
Social media addiction is a behavior that always accesses social media while ignoring other activities so that many bad things can be detrimental. The increasing use of gadgets among students to adults indicates that this behavior is rampant. If this continues to increase, communication with other people or the surrounding environment will be directly disrupted. This research procedure uses classroom action research where the stages carried out are 4, namely planning, action, observation, and reflection. The social media addiction instrument used is adopted from the